Impact of Financial Risk and Macro-Economic Variable on Stock Return: Evidence from Commercial Banks of Nepal - Dhakal, Dipendra Raj; Shrestha, Sabin; Shrestha, Anil (Janabhawana Research Journal, 2024)
This paper examines the impact of financial risks and macroeconomic variables on the stock returns of commercial banks in Nepal. The study focuses on four main types of financial risks: credit risk, market risk, capital risk, and liquidity risk, alongside bank size, return on assets (ROA), and dummy variables for COVID-19 and earthquake impacts. Additional macroeconomic variables include economic growth, inflation, and interest rates. Using panel data regression on yearly data over 11 years for 20 commercial banks, the study investigates these factors’ causal impacts on stock returns. The findings indicated that capital risk and liquidity risk negatively affect stock returns, suggesting that higher capital adequacy ratios limit high-risk, high-return investments, and higher liquidity risks lead to financial instability. Credit risk and market risk, however, did not impact stock returns. Larger banks faced negative stock returns, likely due to management complexities and inefficiencies. Economic growth and inflation positively impacted stock returns, reflecting economic optimism and increased activities, while higher interest rates negatively affected returns by increasing borrowing costs. The COVID-19 pandemic had a positive impact due to increased stock market activity amid limited investment opportunities, whereas the 2015 earthquake negatively affected returns as efforts focused on rebuilding. These insights underscore the need for robust risk management and consideration of broader economic conditions in investment and policy decisions.